Uma análise da usabilidade e experiência do usuário do Banco Inter. - Linhares Filho, Reinaldo da Cunha (2022)
This work aims to present an evaluation of usability and user experience of a digital banking system. Digital banking systems are characterized by a technological innovation in the financial sector, transforming the entire financial service into a digital client format, from account opening to personal service. There is a diversity of use of its systems, an emphasis on the quality of all public services that satisfy the quality of its objectives and simple needs of its objectives. In this work, an evaluation of usability and user experience was carried out in the digital banking system, Banco Inter, responsible for services such as free digital account, investment, insurance and credit platform. After the evaluation, the results were analyzed in order to propose improvements in the obtained system Banco Inter.